Development of Ni-based catalysts via microemulsion synthesis approach for methane dry reforming / Muhammad Usman Rashid - Muhammad Usman , Rashid (2017)

(untitled)
Dry reforming of methane has drawn increased attention as it utilizes inexpensive, local source of energy; landfill gas, containing considerable amounts of methane and carbon dioxide produced by anaerobic decomposition of municipal solid waste. In this study, microemulsion synthesis approach was adopted to synthesize Ni-based catalysts supported on MgO and CeO2. The investigation on the various synthesis parameters effecting Ni metal surface area such as: water-to-surfactant ratio (0.33, 0.5 and 0.66), aging time (0.5 to 24 h), calcination temperature (450 to 1000 oC) and Ni metal molar concentration (2 M to 7 M) exhibited that favourable parameters for the achievement of higher Ni surface area are the low calcination temperature (450 oC), moderate aging time (2 h) and lower Ni metal molar concentration (2 M). Furthermore, at constant water-to-surfactant ratio, an increase in water content leads to the decrease in surface area due to the higher micellar exchange rate favouring the growth of larger particles. 20%Ni/MgO catalyst exhibited higher methane (49.93 %) and carbon dioxide (54.80 %) conversion compared to pure Ni particles (18.72% CH4 and 21.80% CO2 conversion). Further study on the influence of calcination temperatures (450 oC, 600 oC and 800 oC) over 20%Ni/MgO catalysts indicated that the increase of calcination temperature (from 450 to 800 oC) leads to the decrease in surface area from 153.22 m2/g to 34.72 m2/g and also exhibits lower stability compared to the catalyst calcined at lower calcination temperature (450 oC). However, when the influence of calcination temperatures (450 oC, 600 oC and 800 oC) on the NiO-MgO solid solution formation was investigated with different Ni metal content (20, 40 and 80 wt%), it was observed that 80%Ni/MgO catalyst calcined at higher temperature (800 oC) exhibited better catalytic activity and stability at a very high weight hourly space velocity (WHSV = 1.68 x 105 ml h-1 g-1). This was attributed to the presence of higher Nio active sites due to higher Ni content and formation of strong NiO-MgO solid solution. The application of higher reduction temperature (800 oC) to 80%Ni/MgO exhibited severe deactivation compared to the catalyst reduced at lower temperature (550 oC). This was attributed to the fact that the catalyst reduced at lower temperature was less prone to sintering. Core-shell like structures (Ni@CeO2) were synthesized at different Ni content (20% Ni, 40% Ni, and 80%Ni) and investigated at reaction temperature of 800 oC and WHSV of 1.2 x 105 ml h-1 g-1. 40% Ni@CeO2 exhibited higher catalytic activity and better stability compared to 20% Ni@CeO2 and 80% Ni@CeO2. This leads to the conclusion that proper balance between Ni active sites and CeO2 content played a critical role in the achievement of higher stability and in the suppression of carbon deposition. Fresh and spent catalysts were characterized by BET, XRD, TPR-H2, TPD-CO2, FESEM and TEM.